Squamous cell cancer of the neck - Hermans, R. (Contemporary issues in cancer imaging, 2008)
Imaging studies provide crucial information on disease extent in head and neck malignancies. A thorough knowledge of the loco-regional anatomy of this complex area and a proper understanding of the natural disease spread pattern are prerequisites in the interpretation of these imaging studies. Tumor extent influences tumor staging, predicts outcome and influences treatment choices. Knowledge of the different treatment options and expected post-therapeutic tissue changes are also critical in order to use imaging adequately in the surveillance of these patients. After an introductory chapter on epidemiology and clinical signs, this book reviews the pertinent imaging findings for each of the major anatomical subsites. Emphasis is on CT and MRI, but PET and ultrasound are also discussed where appropriate. Reviews on modern surgical and radiotherapeutic techniques are included, helping the reader to understand post-treatment tissue changes and how to differentiate these from tumor recurrence or treatment complications.
Keywords: Neck : Cancer : Imaging; Squamous cell carcinoma : Imaging